Adolescent and parental proxy online record access: analysis of the empirical evidence based on four bioethical principles - Josefin Hagström; Maria Hägglund; Charlotte Blease (BMC Medical Ethics)
Abstract Background During recent decades, providing patients with access to their electronic health records (EHRs) has advanced in healthcare. In the European Union (EU), the General Data Protection Regulation provides individuals with the right to check their data in registries such as EHRs. A proposal for a European Health Data Space has been launched, which will further strengthen patients’ right to have online access to their EHRs throughout Europe. Against these policy changes, scant attention has been paid to the ethical question about whether adolescents and parents should access the adolescent’s EHR, and if so, under what conditions. Methods In this paper, we apply biomedical ethical principles to explore key questions about adolescents’ and parents’ access to adolescents’ EHRs, with the aim of informing future discussions about the development of ethical and policy practice guidelines. Results Drawing on current empirical research, we find preliminary evidence that in some contexts, patient online record access (ORA) could help to facilitate autonomy for adolescents and parents as well as offering support in managing appointments and medications. Notably, however, we find contrasting perspectives between adolescents’ and parents’ experienced benefits and healthcare professionals’ (HCPs) perceived potential harm, with the latter worried about decreased documentation quality after access. Concerns about capacity to understand their health information, and increased anxiety among adolescents obstruct the support of adolescent autonomy among parents and HCPs. Still, research is limited, particularly with respect to adolescents’ experiences of reading their EHRs, and differences across settings have not been closely examined. Conclusions To advance more comprehensive understanding of the effects of ORA, and to inspire greater attention to, and development of, evidence-informed ethical guidance in this domain of clinical practice, we outline a range of empirical questions regarding adolescents’ and parents’ experiences that now warrant further study.